Prevalence and Risk Factors of Deep Vein Thrombosis in Patients Undergoing Lumbar Interbody Fusion Surgery: A Single-Center Cross-Sectional Study. Issue 48 (December 2015) - Yang, Si-Dong; Ding, Wen-Yuan; Yang, Da-Long; Shen, Yong; Zhang, Ying-Ze; Feng, Shi-Qing; Zhao, Feng-Dong
Abstract : Abstract: This cross-sectional study was designed to obtain the current prevalence of deep vein thrombosis (DVT) and analyze related risk factors in patients undergoing lumbar interbody fusion. Medical record data were collected from Department of Spinal Surgery, The Third Hospital of Hebei Medical University, between July 2014 and March 2015. Both univariate analysis and binary logistic regression analysis were performed to determine risk factors for DVT. A total of 995 patients were admitted into this study, including 484 men and 511 women, aged from 14 to 89 years old (median 50, IQR 19). The detection rate of lower limb DVT by ultrasonography was 22.4% (223/995) in patients undergoing lumbar interbody fusion. Notably, average VAS (visual analog scale) score in the first 3 days after surgery in the DVT group was more than that in the non-DVT group ( Z = −21.69, P < 0.001). The logistic regression model was established as logit P = −13.257 + 0.056*X1 − 0.243*X8 + 2.085*X10 + 0.001*X12, (X1 = age; X8 = HDL; X10 = VAS; X12 = blood transfusion; x 2 = 677.763, P < 0.001). In conclusion, advanced age, high postoperative VAS scores, and blood transfusion were risk factors for postoperative lower limb DVT. As well, the logistic regression model may contribute to an early evaluation postoperatively to ascertain the risk of lower limb DVT in patients undergoing lumbar interbody fusion surgery.